Changing household income in rural Indonesia 1995-2007 - Sudaryanto, Tahlim (2010)
This paper examines the structure of household income and its changes in rural areas of Indonesia during the period 1995-2007. Empirical results based on panel data during that period showed that household income grew by 1.7 percent per annum. Household income in estate crops-based villages was higher than that in food crop-based villages. Along with the changes in income level, there have been some changes also in income structures. Although varied across villages, sources of income changes mostly in came from nonfarm sectors. In addition to the changes in employment participation rate, an important source of income in rural areas was remittances from laborers working in the city and overseas. The nonagricultural sector in rural areas are the promotion of the production of high-value commodities coupled with diversification of farm households into nonfarm activities.
Keywords: Households -- Economic aspects; Diversification